Процена на манипулативната вештина на рацете и диференцираност на моторика на прсти кај деца со аутизам - Богдановски, Бојан (Филозофски факултет, Скопје, 2021)
Problem under study: We live in a time when developmental disorders are conditions that are becoming more common and that require more adequate, more effective and professional treatment. ASD is a group of pervasive developmental disorders, followed by disorders in social interactions, verbal and non-verbal communication, and stereotypical and repetitive behaviors. The assessment of the manipulative dexterity of the hands and the differentiation of the fingers motility in children with ASD is of particular importance, because they are closely related to the speech - language, emotional and intellectual development of the child, and they are often impaired or underdeveloped in these people. The main objective of the study is to obtain data on the manipulative dexterity of the hands and the differentiation of finger motility in children with ASD who live in the territory of the Republic of North Macedonia or attend rehabilitation treatment in the capital of the Republic of North Macedonia - Skopje, and to recommend appropriate rehabilitation treatment for the development and stimulation of the manipulative dexterity of the hands and the differentiation of finger motility in children with ASD. Other goals and 6 hypotheses are set. Material and Methods: A research was conducted in the form of a professional, special education observation and assessment of the manipulative dexterity of the hands and differentiation of the finger motility of children with ASD living on the territory of the city of Skopje, using the method for: assessment of the manipulative dexterity of the hand (LAFAYE), assessment of finger motor differentiation (REY) and method of assessment of finger motor differentiation (BUCHE). After the completion of the recommended rehabilitation treatment consisting of exercises for development and stimulation of the manipulative dexterity of the hands and differentiation of the fingers motility, a re-evaluation was performed in order to evaluate the benefits of the treatment. Knowledge of ASD and the importance of manipulative dexterity of the hands and differentiation of finger motility between persons who have direct contact with children with ASD and /or are involved in the treatment of children with ASD in the city of Skopje, are assessed using an anonymous original paper questionnaire survey and telephone interview. Results: The first part of the research that was conducted among people who have direct contact with children with ASD on a daily basis indicates that awareness and knowledge about autism are significantly increased in our country. However, according to the obtained data, 65% of the respondents do not know what MHD and DFM were, and 55% of the respondents do not know how the treatment of MHD and DFM would help children with ASD, we find that this issue is underdeveloped and implemented. in the process of assessment, diagnosis and treatment by our professionals. Data from the assessment of the MHD in children with ASD (LAFAYE), which indicate that 39% of respondents have not developed MHD and 24% of respondents have underdeveloped MHD, i.e. 61% of 100 respondents have a disorder of MHD, are sufficient evidence to tell us that the MHD is disturbed in children with ASD. The results of the assessment of the DFM (REY) showed that 9% of the respondents have a well-developed DFM, 33% have an underdeveloped DFM, and 58% of the respondents have not developed a DFM, i.e. 91% of the respondents have underdeveloped DMP. This data indicates that DFM is disturbed in children with ASD. The results of this assessment of the DFM (BUCHE) showed that 22% of the respondents have a well-developed DFM, 20% have an underdeveloped DFM, and 58% of the respondents have not developed DFM, i.e. 78% of the respondents have disorder of DFM. This data indicates that DFM is disturbed in children with ASD. The data obtained from this research showed that MHD and DFM are significantly impaired in female children with ASD compared to male children with ASD, and that MHD and DFM are significantly impaired in children with ASD who are of preschool age compared to children with ASD on school age. The data obtained from the control assessment of the MHD and DFM after the application of the treatment for development and stimulation of the MHD and DFM, showed that the treatment has a positive impact on the MHD and DFM and the overall condition of children with ASD. Discussion: This research, i.e. this study is one of the few in our country that aims to prove the importance of the MHD and DFM in children with ASD, i.e. the importance of the assessment of the MHD and DFM in children with ASD. The assessment of the MHD and the DFM in children with ASD, which is essentially the main goal and the main research in this study, we believe has brought new knowledge and challenges for the Macedonian scientific activity and for Macedonian professionals who working with children with ASD. The data from this research indicated that the MHD and DFM are significantly impaired in children with ASD, significantly impaired in female children with ASD and significantly impaired in children with ASD in preschool age, which confirms the link between motor disorders and speech and language, social and cognitive abilities in people with ASD. To our great satisfaction, the results of the third research to assess the success of treatment, i.e. exercises for development and stimulation of the MHD and DFM, indicated a positive impact of rehabilitation treatment, not only on the MHD and DFM, also on the overall condition of children with ASD. Of course, we hope that this scientific research will be a stimulus for new Macedonian scientific research related to this issue. Conclusion: Based on the results of the research, we can conclude that the manipulative dexterity of the hands and the differentiation of finger motility in children with ASD are significantly impaired, so the assessment of the MHD and DFM is extremely important in the special education and rehabilitation of these people and in forming a plan and program for rehabilitation treatment, which is highly benefitial for the condition of these persons. Recommendations: It is recommended to organize educational campaigns with media coverage to acquaint the population with ASD and the importance of manipulative hand dexterity and differentiation of finger motility for child development, as well as creating a standardized plan and program consisting of exercises for rehabilitation of MHD and DFM.
Магистерска теза одбранета во 2021 година на Филозофскиот факултет во Скопје, под менторство на проф. д–р Горан Ајдински.
Keywords: manual dexterity, finger motility, autism spectrum disorders, autism, special education, rehabilitation, assessment, treatment.